Spatial analysis of primary education services in the district of Kufa for the period (2010-2022) and their development until the year (2050) - Dr.Lama Abdul Manaf; Dr. Ali Lafta Saeeda.; Dr. Rahim Mohamed Abdel Zaid (Journal of College of Education, 2023)
Educational services in our current era are the necessary services that must be provided to the community, as they are the basis for the progress and development of societies, and it is a very important criterion for measuring the extent of backwardness and progress of those societies. Therefore, educational services can be considered among the important and necessary services provided by the city to its residents and residents of its regions. In addition to the fact that education is one of the important factors behind the prosperity and development of society by providing it with productive minds in all aspects of life, and the fate and future of society depends on them to a large extent. From a positive return that transcends society towards progress. Primary education is one of the most important educational services provided by the city, as it represents the first scientific building block that a student gets in his prime. Therefore, the researchers generated the idea of this research, which includes three investigations. The first dealt with the geographical distribution of primary education services in the district of Kufa, while the second dealt with the efficiency of this The type of services, while the third section examined the development of primary education services in the district until 2050, and the research concluded a set of conclusions, the most important of which is the random geographical distribution of primary education services. More primary schools in the target year 2050, which must be available in order to improve the status of primary education services in order to achieve their future development.
Keywords: : تحليل مكاني ، الخدمات التعليمية ، مدينة الكوفة .